Modulation of Donor-Acceptor Distance in a Series of Carbazole Push-Pull Dyes; A Spectroscopic and Computational Study - Joshua J. Sutton; Jonathan E. Barnsley; Joseph I. Mapley; Pawel Wagner; David L. Officer; Keith C. Gordon (Molecules, 2018)
A series of eight carbazole-cyanoacrylate based donor-acceptor dyes were studied. Within the series the influence of modifying the thiophene bridge, linking donor and acceptor and a change in the nature of the acceptor, from acid to ester, was explored. In this joint experimental and computational study we have used electronic absorbance and emission spectroscopies, Raman spectroscopy and computational modeling (density functional theory). From these studies it was found that extending the bridge length allowed the lowest energy transition to be systematically red shifted by 0.12 eV, allowing for limited tuning of the absorption of dyes using this structural motif. Using the aforementioned techniques we demonstrate that this transition is charge transfer in nature. Furthermore, the extent of charge transfer between donor and acceptor decreases with increasing bridge length and the bridge plays a smaller role in electronically mixing with the acceptor as it is extended.